1999
DOI: 10.1038/sj.bjc.6694262
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of haematogenous metastasis of colon cancer in mice by a selective COX-2 inhibitor, JTE-522

Abstract: in colorectal tumours and play a role in colorectal tumorigenesis. Recently it has been reported that selective inhibition of COX-2 inhibits colon cancer cell growth. In this study we investigated the effect of a selective COX-2 inhibitor (JTE-522) on haematogenous metastasis of colon cancer. For this purpose, we selected a murine colon cancer cell line, colon-26, that constitutively expresses the COX-2 protein. The subclone P expressed a high level of COX-2 and the subclone 5 expressed a low level. The colon-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
73
2
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(80 citation statements)
references
References 28 publications
4
73
2
1
Order By: Relevance
“…A previous in vitro study using cell lines of CRC origin by Tsujii et al (1997) suggested that COX-2 inhibition may be beneficial in preventing the expression of genes associated with metastatic progression. Furthermore, a recent study by Tomozawa et al (1999) demonstrated that the COX-2 selective inhibitor JTE-522 might decrease the rate of haematogenous metastasis of CRC.…”
Section: Discussionmentioning
confidence: 99%
“…A previous in vitro study using cell lines of CRC origin by Tsujii et al (1997) suggested that COX-2 inhibition may be beneficial in preventing the expression of genes associated with metastatic progression. Furthermore, a recent study by Tomozawa et al (1999) demonstrated that the COX-2 selective inhibitor JTE-522 might decrease the rate of haematogenous metastasis of CRC.…”
Section: Discussionmentioning
confidence: 99%
“…In the mouse model, JTE-522 has been found to inhibit liver and lung metastases of colon cancer that show COX-2 expression but lack an effect on those lacking COX-2 expression. 16,17 Considering that COX-2 is the best-known target for NSAIDs in colon carcinogenesis, lack of inhibitory effects of JTE-522 on signet-ring cell and mucinous carcinomas could be explained at least in part by a lack of COX-2 expression in those cancers. Furthermore, Park et al 25 have suggested that tubular adenocarcinoma follows the ACF-adenoma-carcinoma sequence, whereas poorly differentiated carcinoma may arise de novo without passing through the stage of ACF in DMH-induced colon carcinogenesis in rats.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 This compound also inhibited liver and lung metastases of colon cancer expressing COX-2 but lacked effect on those lacking COX-2 expression in the nude mouse xenograft model. 16,17 In chemically induced colon carcinogenesis, we have previously shown that JTE-522 inhibited the development of aberrant crypt foci (ACF), the putative precursors of both human and experimental colon cancer, 18,19 when administered throughout the study. 20 In the present study, to evaluate the chemopreventive properties of JTE-522, we have investigated the efficacy of JTE-522 during different stages of rat colon carcinogenesis using colon tumor formation as an endpoint, including its effects on histopathologic pattern and growth, as well as invasion of colon tumors.…”
mentioning
confidence: 99%
“…In the treatment experiment, a hepatic metastasis model was constructed by infusing cancer cells in BALB/c or CDF1 male mice below the splenic capsule where etodolac and PSK were administered. Cells (5x10 5 ) of the mouse colon cancer 26 cell line (CT26) and its highly metastatic variant were implanted below the splenic capsule. Three days after implantation, a spleen-removed group and a non-spleen-removed one were produced and the hepatic metastasis model was designed.…”
Section: Methodsmentioning
confidence: 99%